2011 IFPRI Annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
Feeding the world’s population, which is expected to reach 9 billion by 2050, is arguably the most important challenge facing policymakers. Amid food price shocks and an unpredictable climate, how we approach even the most basic components of food security—what to eat and how to grow it—comes into question. To find lasting solutions to hunger, malnutrition, and poverty, we need to reassess how to meet the rising demand for food without generating large food price increases. Through its rigorous, wide-ranging policy research, the International Food Policy Research Institute (IFPRI) works to clarify options and identify solutions.